IPSC screening for drug repurposing identifies anti‐RNA virus agents modulating host cell susceptibility. Issue 5 (6th April 2021) - Imamura, Keiko; Sakurai, Yasuteru; Enami, Takako; Shibukawa, Ran; Nishi, Yohei; Ohta, Akira; Shu, Tsugumine; Kawaguchi, Jitsutaro; Okada, Sayaka; Hoenen, Thomas; Yasuda, Jiro; Inoue, Haruhisa
Abstract : Human pathogenic RNA viruses are threats to public health because they are prone to escaping the human immune system through mutations of genomic RNA, thereby causing local outbreaks and global pandemics of emerging or re‐emerging viral diseases. While specific therapeutics and vaccines are being developed, a broad‐spectrum therapeutic agent for RNA viruses would be beneficial for targeting newly emerging and mutated RNA viruses. In this study, we conducted a screen of repurposed drugs using Sendai virus (an RNA virus of the family Paramyxoviridae ), with human‐induced pluripotent stem cells (iPSCs) to explore existing drugs that may present anti‐RNA viral activity. Selected hit compounds were evaluated for their efficacy against two important human pathogens: Ebola virus (EBOV) using Huh7 cells and severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) using Vero E6 cells. Selective estrogen receptor modulators (SERMs), including raloxifene, exhibited antiviral activities against EBOV and SARS‐CoV‐2. Pioglitazone, a PPARγ agonist, also exhibited antiviral activities against SARS‐CoV‐2, and both raloxifene and pioglitazone presented a synergistic antiviral effect. Finally, we demonstrated that SERMs blocked entry steps of SARS‐CoV‐2 into host cells. These findings suggest that the identified FDA‐approved drugs can modulate host cell susceptibility against RNA viruses. Abstract : FDA‐approved drugs, identified by iPSC screening with Sendai virus, exhibited inhibitory effects on the infection of Huh7 cells by Ebola virus and of Vero E6 cells by SARS‐CoV‐2. These drugs, with efficacy in different combinations of RNA viruses and cells, may have therapeutic potential for RNA virus infections, including newly emerging and mutated viruses, by modulating host cell susceptibility.